SAR11 Cells Rely on Enzyme Multifunctionality To Metabolize a Range of Polyamine Compounds - Stephen E. Noell (American Society for Microbiology, 2021)
ABSTRACT In the ocean surface layer and cell culture, the polyamine transport protein PotD of SAR11 bacteria is often one of the most abundant proteins detected. Polyamines are organic cations at seawater pH produced by all living organisms and are thought to be an important component of dissolved organic matter (DOM) produced in planktonic ecosystems. We hypothesized that SAR11 cells uptake and metabolize multiple polyamines and use them as sources of carbon and nitrogen. Metabolic footprinting and fingerprinting were used to measure the uptake of five polyamine compounds (putrescine, cadaverine, agmatine, norspermidine, and spermidine) in two SAR11 strains that represent the majority of SAR11 cells in the surface ocean environment, “Candidatus Pelagibacter” strain HTCC7211 and “Candidatus Pelagibacter ubique” strain HTCC1062. Both strains took up all five polyamines and concentrated them to micromolar or millimolar intracellular concentrations. Both strains could use most of the polyamines to meet their nitrogen requirements, but polyamines did not fully substitute for their requirements of glycine (or related compounds) or pyruvate (or related compounds). Our data suggest that potABCD transports all five polyamines and that spermidine synthase, speE, is reversible, catalyzing the breakdown of spermidine and norspermidine, in addition to its usual biosynthetic role. These findings provide support for the hypothesis that enzyme multifunctionality enables streamlined cells in planktonic ecosystems to increase the range of DOM compounds they metabolize. IMPORTANCE Genome streamlining in SAR11 bacterioplankton has resulted in a small repertoire of genes, yet paradoxically, they consume a substantial fraction of primary production in the oceans. Enzyme multifunctionality, referring to enzymes that are adapted to have broader substrate and catalytic range than canonically defined, is hypothesized to be an adaptation that increases the range of organic compounds metabolized by cells in environments where selection favors genome minimization. We provide experimental support for this hypothesis by demonstrating that SAR11 cells take up and metabolize multiple polyamine compounds and propose that a small set of multifunctional enzymes catalyze this metabolism. We report that polyamine uptake rates can exceed metabolic rates, resulting in both high intracellular concentrations of these nitrogen-rich compounds (in comparison to native polyamine levels) and an increase in cell size.